Resonance Raman and fourier transform infrared detection of azide binding to the binuclear center of cytochrome bo3, oxidase from Escherichia coli - Vamvouka, Magdalini; Varotsis, Constantinos (My University, 1999)
Resonance Raman and FTIR spectra are reported for the oxidized azide-bound derivative of the quinol cytochrome bo3 oxidase from Escherichia coli. The resonance Raman spectra display three isotope-dependent vibrational modes at 419, 2040, and 2061 cm-1. The FTIR spectra display two isotope-dependent bands at 2040 and 2061 cm-1. We assign the band at 419 cm-1 to v(Fe-N3-CuB) and the bands at 2040 and 2061 cm-1 to Vas(N3). The observation of two vas(N3) modes suggests that the azide ion binds to two different enzyme conformations, both forming bridging complexes with the binuclear center. Comparison of the FTIR data of the azide-bound cytochrome bo3 and cytochrome aa3 complexes reveal that there are quantitative differences in the structure of the heme o3-CuB and heme a3-CuB binuclear pockets upon azide binding. The present data on the vibrational frequencies of the azide-bound cytochrome bo3 complex do not support the recent proposal that azide binds as a terminal ligand to CuB (Little, R. H.; Cheesman, M. R.; Thomson, A. J.; Greenwood, C.; Watmough, N. J. Biochemistry 1996, 35, 13780-13787) but are more reasonably interpreted to conclude that azide functions as a bridge between heme o3 and CuB
Keywords: Fourier transform infrared spectroscopy; Azides; Cytochrome oxidase; Escherichia coli; Heme